Novel functions of an iron-sulfur flavoprotein from Trichomonas vaginalis hydrogenosomes - Smutná, Tamara; Pilarová, Katerina; Tarábek, Ján; Tachezy, Jan; Hrdý, Ivan (Antimicrobial agents and chemotherapy, 2014)
Iron-sulfur flavoproteins (Isf) are flavin mononucleotide (FMN)- and FeS cluster-containing proteins commonly encountered in anaerobic prokaryotes. However, with the exception of Isf from Methanosarcina thermophila, which participates in oxidative stress management by removing oxygen and hydrogen peroxide, none of these proteins has been characterized in terms of function. Trichomonas vaginalis, a sexually transmitted eukaryotic parasite of humans, was found to express several iron-sulfur flavoprotein (TvIsf) homologs in its hydrogenosomes. We show here that in addition to having oxygen-reducing activity, the recombinant TvIsf also functions as a detoxifying reductase of metronidazole and chloramphenicol, both of which are antibiotics effective against a variety of anaerobic microbes. TvIsf can utilize both NADH and reduced ferredoxin as electron donors. Given the prevalence of Isf in anaerobic prokaryotes, we propose that these proteins are central to a novel defense mechanism against xenobiotics.
Keywords: geny hub; Drug Resistance; NAD; vodík; Hydrogen; Ferredoxins; molekulární sekvence - údaje; Amino Acid Sequence; Metronidazole; ferredoxiny; léková rezistence; Flavoproteins; Antitrichomonal Agents; Iron-Sulfur Proteins; Trichomonas vaginalis; Genes, Fungal; proteiny obsahující železo a síru; metronidazol; subcelulární frakce; antitrichomonádové látky; sekvence aminokyselin; Catalysis; Molecular Sequence Data; flavoproteiny; katalýza; Subcellular Fractions